Challenging hierarchies in Anglophone Cameroon literature: women, power and visions of change in Bole Butake's plays - Nkealah, Naomi Epongse (My University, 2011)
Through an in-depth analysis of selected texts, this study engages with the ways in which the Anglophone Cameroonian playwright, Bole Butake, interprets questions of gender, sex and female power. The study traces the evolution of Butake’s vision of women from his first play Betrothal without Libation (1982) to his latest play Family Saga (2005). The analysis focuses on how women construct power in the imaginary worlds of Butake’s writing and how, in turn, power is constructed through them. Questions of femininities and masculinities are probed in an effort to determine the writer’s ideological leanings. Using a feminist framework, particularly that postulated by acclaimed scholar Florence Stratton (1994), this work engages with Butake’s nine published plays with the simple objective of deconstructing the different layers of meanings embedded in the dramatic narratives’ construction of power politics within urban and rural spaces. This study aims to critique not only Butake’s use of imagery, allegory and other narrative techniques in his creative imagining of women’s identities, but also the gender implications of hierarchical formations within the worlds of Butake’s plays. Essentially, the thesis looks at Butake’s constructions of female power and women’s agency and the implications these have on feminist discourses.
Keywords: Bole Butake; Women; Cameroon; Literature; Plays